Solving the Coupled System Improves Computational Efficiency of the Bidomain Equations - Southern, J; Plank, G; Vigmond, E; Whiteley, J (2009)

(untitled)
The bidomain equations are frequently used to model the propagation of cardiac action potentials across cardiac tissue. At the whole organ level the size of the computational mesh required makes their solution a significant computational challenge. As the accuracy of the numerical solution cannot be compromised, efficiency of the solution technique is important to ensure that the results of the simulation can be obtained in a reasonable time whilst still encapsulating the complexities of the system. In an attempt to increase efficiency of the solver, the bidomain equations are often decoupled into one parabolic equation that is computationally very cheap to solve and an elliptic equation that is much more expensive to solve. In this study the performance of this uncoupled solution method is compared with an alternative strategy in which the bidomain equations are solved as a coupled system. This seems counter-intuitive as the alternative method requires the solution of a much larger linear system at each time step. However, in tests on two 3-D rabbit ventricle benchmarks it is shown that the coupled method is up to 80% faster than the conventional uncoupled method — and that parallel performance is better for the larger coupled problem.